PEMBUATAN BIODIESEL DARI MINYAK GORENG BEKAS DENGAN METODE TRANSESTERIFIKASI - Anang Fatkhul; Moh. Arif Batutah; Irwan Syahrir; Ponidi (Universitas Muhammadiyah Surabaya, 2023)
Biodiesel is an environmentally friendly alternative fuel for diesel engines in the form of triglyceride compounds derived from renewable resources in the form of vegetable oils and animal fats. The production of biodiesel uses used cooking oil left over from frying food which is reacted with a solution of KOH and Methanol as a base catalyst. The process of carrying out this research began with the stage of making Biodiesel products from used cooking oil using the transesterification method, at this stage used cooking oil was reacted with potassium hydroxide (KOH) mixed with Methanol, with a reaction ratio of 500 : 125 : 0.5 and 500 : 125 : 1%, then stirring for 1 hour with a temperature range of 50 °C - 60 oC, the next step is the analysis stage. At this stage of the analysis, the viscosity test was carried out with the results obtained being 5.8mm²/s for 0.5% KOH mixing, and 3.5mm²/s for 1% KOH mixing. density test (density), the results obtained were 874 g/cm³ for mixing 0.5% KOH and 890g/cm³ for mixing 1% KOH, and the flash point test (flash point), with the results obtained was 182°C for mixing 0.5% KOH and 177°C for mixing 1% KOH then analyzing how the effect of KOH levels on the characteristics of biodiesel products from used cooking oil. Keywords: Used cooking oil, Biodiesel, KOH catalyst